Activity of Some Novel Chalcone Substituted 9-anilinoacridines against Coronavirus (COVID-19): A Computational Approach - Kalirajan, Rajagopal (Coronaviruses, 2020)
Background: In the year earlier part of 2020, many scientists urged to discover novel drugs against for the treatments of COVID-19. Coronavirus Disease 2019 (COVID-19), a life-threatening viral disease, was discovered first in China and quickly spread throughout the world. Objective: In the present article, some novel chalcone substituted 9-anilinoacridines (1a-z) were developed by in silico studies for their COVID19 inhibitory activity. Molecular docking studies of the ligands 1a-z were performed against COVID19 (PDB id - 5R82) targeting the coronavirus using Schrodinger suite 2019-4. Methods: The molecular docking studies were performed by the Glide module and the binding energy of ligands was calculated using the PRIME MM-GB/SA module of Schrodinger suite 2019-4. Results: From the results, many compounds are significantly active against COVID19 with a Glide score of more than -5.6 when compared to the currently used drug for the treatment of COVID19, Hydroxychloroquine (-5.47). The docking results of the compounds exhibited similar mode of interactions with COVID19 and the residues, THR25, THR26, LEU27, SER46, MET49, HIE41, GLN189, ARG188, ASP187, VAL186, HIE164, ASN142, and GLY143 play a crucial role in binding with ligands. MMGBSA binding calculations of the most potent inhibitors are more stably favourable. Conclusion: From the results of in-silico studies, it provides strong evidence for the consideration of valuable ligands in chalcone substituted 9-anilinoacridines as potential COVID19 inhibitors and the compounds, 1x,a,r,s with significant Glide scores may produce significant COVID19 activity for further development, which may prove their therapeutic potential.
Keywords: MM-GBSA